2009
DOI: 10.1002/ejic.200801151
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Silicon Bond Activation by [Pd(ItBu)2] – the Molecular Structures of [Pd(Me3Si)(ItBu)(μ‐I)]2 and [Pd(CH2ItBu)I2]

Abstract: The reaction of Me 3 SiCH 2 I with [Pd(ItBu) 2 ] (ItBu = 1,3-ditert-butyl-imidazol-2-ylidene) results, not in simple oxidative addition, but in carbon-silicon bond activation and formation of [Pd(Me 3 Si)(ItBu)(µ-I)] 2 (2) and [Pd(CH 2 ItBu)I 2 ] (3). The zwitterionic nature of the latter has been confirmed by DFT studies, and a possible mechanism for the formation of these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…This compound is the first monomeric palladium complex resulting from oxidative addition of a silicon–halide bond to be characterized, and is also the first such complex to be supported by a phosphine ancillary ligand. 20 This complex was fully characterized in solution ( 1 H, 13 C and 31 P NMR in CD 2 Cl 2 at 0 °C), and the data are consistent with the structure shown in Figure 6 .…”
Section: Results and Discussionsupporting
confidence: 74%
“…This compound is the first monomeric palladium complex resulting from oxidative addition of a silicon–halide bond to be characterized, and is also the first such complex to be supported by a phosphine ancillary ligand. 20 This complex was fully characterized in solution ( 1 H, 13 C and 31 P NMR in CD 2 Cl 2 at 0 °C), and the data are consistent with the structure shown in Figure 6 .…”
Section: Results and Discussionsupporting
confidence: 74%
“… 122 Reaction of complex 42 with Me 3 SiCl affords compound 43 ( Scheme 9 ). 108 A similar adduct was detected by NMR in a C 6 D 6 solution of [Pd(I t Bu) 2 ] complex and Me 3 SiI after 40 day storage at room temperature; 175 the authors suggested that the NHC–SiMe 3 adduct was formed via Pd–NHC dissociation and subsequent reaction of the free NHC with Me 3 SiI. Facile reactions of PCl 3 , PBr 3 , SbCl 3 and AsCl 3 with Li/NHC adducts 44 afford the corresponding P–NHC, Sb–NHC and As–NHC products 45 ( Scheme 9 ).…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 82%
“…Such kinds of complexes are also known in the literature. 44 Since the methylene proton in 1a is the most acidic proton, it is obvious that 2a should be formed easily. In fact, in the preparation of 2a, the zwittterion and the side product trans-PdCl 2 (py) 2 were formed exclusively even after prolonged heating at 80°C overnight, indicating that 2a is either kinetically stable or is indeed the thermodynamic product.…”
Section: ■ Results and Discussionmentioning
confidence: 99%